2019
DOI: 10.1016/j.astropartphys.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential for measuring the longitudinal and lateral profile of muons in TeV air showers with IACTs

Abstract: Muons are copiously produced within hadronic extensive air showers (EAS) occurring in the Earth's atmosphere, and are used by particle air shower detectors as a means of identifying the primary cosmic ray which initiated the EAS. Imaging Atmospheric Cherenkov Telescopes (IACTs), designed for the detection of γ-ray initiated EAS for the purposes of Very High Energy (VHE) γ-ray astronomy, are subject to a considerable background signal due to hadronic EAS. Although hadronic EAS are typically rejected for γ-ray a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Such tests might be developed for air shower arrays such as HAWC or future facilities such as SGSO, however some assumptions of the cosmic ray composition would have to be made. Muon LDF and production height measurements should also be possible with the Cherenkov telescope array [27], however measurements in the 100 ĠeV to 1 TeV range may be challenging. Particularly the combination of ground particles and Cherenkov light measured by LHAASO may help to better distinguish between model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Such tests might be developed for air shower arrays such as HAWC or future facilities such as SGSO, however some assumptions of the cosmic ray composition would have to be made. Muon LDF and production height measurements should also be possible with the Cherenkov telescope array [27], however measurements in the 100 ĠeV to 1 TeV range may be challenging. Particularly the combination of ground particles and Cherenkov light measured by LHAASO may help to better distinguish between model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…2. A thorough study of the different muon identification techniques and their performance is beyond the scope of this paper (see [12,21,22] for some recent efforts). Current background rejection methods implemented in IACTs rely on the properties of the time-integrated Cherenkov light images.…”
Section: Detectable Muons In Showersmentioning
confidence: 99%
“…The ring-like images produced when ground-level muons pass through IACTs have long been used as a means of calibration [10], see [11] for a recent review. Recently, [12] suggested that the identification of a much higher fraction (2021) 81:1101 Large telescopes such as the central telescope of H.E.S.S. [13] and the Large-Sized Telescopes (LSTs) of CTA [14] enable the detection of individual muons out to large impact distance.…”
Section: Introductionmentioning
confidence: 99%
“…Muon identification can be carried out via different techniques, which exploit the properties of the muon Cherenkov signal described in Section 2. A thorough study of the different muon identification techniques and their performance is beyond the scope of this paper (see [12,21,22] for some recent efforts). Current background rejection methods implemented in IACTs rely on the properties of the time-integrated Cherenkov light images.…”
Section: Detectable Muons In Showersmentioning
confidence: 99%
“…The ring-like images produced when ground-level muons pass through IACTs have long been used as a means of calibration [10], see [11] for a recent review. Recently, [12] suggested that the identification of a much higher fraction of muons produced in extensive air showers is possible with IACTs.…”
Section: Introductionmentioning
confidence: 99%